FV 1. Perilesional activation in poststroke language recovery. Issue 9 (September 2016) - Stockert, A.; Klingbeil, J.; Wawrzyniak, M.; Wrede, K.; Saur, D.
Abstract : Background: Poststroke aphasia recovery evolves in time. Increased perilesional activity associated with treatment-related language improvements has been confirmed in the chronic phase (Fridriksson et al., 2011 ), but has not yet been systematically demonstrated during the early phases of stroke recovery. The pathophysiology of stroke suggests that perilesional reorganisation evolves within days, lasting for months after stroke, while increased neuronal excitability might provide a basis for perilesional neuroplasticity (Schiene et al., 1999 ). Methods: We compared fMRI BOLD response to speech (SP) and reversed speech (REV) using an auditory comprehension paradigm (Saur et al., 2006 ) administered repeatedly (acute ( t 1)  ⩽  1 week, subacute ( t 2) = 1–2 weeks, chronic ( t 3) > 6 months post-onset) to patients with stroke affecting left frontal (FC, N  = 17) or temporoparietal cortex (TPC, N  = 17). Language activation (SP > REV) obtained from three perilesional ROIs expanding stepwise to 39 mm beyond the lesion (DISTANCE) was compared across TIME and to the improvement of language comprehension/production. Results: An ANOVA revealed a significant TIME × DISTANCE interaction ( F (4) = 2.9, p  = .025) with increased activation from t 1 to t 3 and t 2 to t 3 (p). Conclusion: To conclude, a remapping of cortical language representations in undamaged left cortices is likely to commence during subacute phase of recovery and improvements of specific language functions differentially involve frontal or temporal perilesional areas.